Agouti overexpression in a transgenic model regulates integrity, permeability and electrogenic amino acid transport in zebrafish intestine - Leal, Esther; Angotzi, Anna Rita; Godino-Gimeno, Alejandra; Gregório, Silvia F.; Rotllant, Josep; Saera-Vila, Alfonso; Fuentes, Juan; Cerdá-Reverter, José Miguel (Frontiers in Marine Science, 2022)
Overexpression of asip1 in transgenic zebrafish disrupts dorsoventral pigment pattern in addition to increasing food intake levels and linear growth. A higher feed intake is unnecessary in transgenic fish to enable larger and heavier growth. A plausible explanation may rely on the enhanced feeding efficiency mediated by improved nutrient absorption in transgenic animals. To test this hypothesis, wide scope transcriptomic techniques were used to elucidate the potential pathways involved in the enhanced nutrient absorption and intestinal epithelium permeability/integrity. In addition, the electrogenic capacity for amino acid transport was analysed. Transcriptomic analysis reveal that amino acid, monocarboxylates, ionic and vitamin transmembrane transporters were substantially modified. Enrichment analysis also revealed an inhibition of intestinal lipid metabolism and down-regulation of KEGG pathways related to membrane integrity suggesting augmented intestinal laxity that may enhance paracellular transport. Electrophysiological experiments carried out in Ussing chambers show that asip1 overexpression decrease membraned tissue resistance (Rt), indicating a modification of the intestinal barrier function in ASIP1 transgenic animals. Similarly, paracellular permeability was higher in transgenic zebrafish. Both the decrease in Rt and the increase in permeability point to an ASIP1-dependent decrease in the tissue barrier function. Electrogenic amino acid transport was also enhanced in transgenic animals providing strong indication that ASIP1 fish can extract more amino acids from their diet at similar feeding levels. Both transcriptomic and electrophysiological results suggest that asip1-overexpressing zebrafish display improved nutrient absorption and by extension a higher feed efficiency which explains enhanced growth in the absence of augmented food intake. The enhanced growth of ASIP1 zebrafish potentially mediated by improved nutrient uptake and feed efficiency suggests that the melanocortin system, specifically asip1 overexpression, is a potential target for the development of genetically engineered fish displaying improved performance and no differential lipid accumulation.